MULTICULTURAL VOCABULARY IN MASS MEDIA IN THE REPUBLIC OF KAZAKHSTAN - A.Zh. Shaikenova,; T.A. Morozova,; K. I. Ibraeva,; K. Rakhmet, (Academic Journal of Physical and Chemical Sciences, 2019)
In conditions of multicultural reality, when people from different linguistic and cultural communities come into contact, the mutual influence and interpenetration of cultures leads to the acculturation of members of societies, connecting in their minds different cultures, focused on another, predisposed to dialogue with him. Language training, combined with familiarization with cultural and social values, can and should serve as a powerful means of understanding between peoples. The idea of multicultural education involves the prevention of misunderstanding arising from the communication of different nationalities. Multicultural education is the basis for combining multicultural ethnic experience, the coexistence of national values and the individual’s right to national-cultural self-expression, the development of which must be instilled in the education system and the media.